2011
DOI: 10.3390/molecules16086271
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Antimicrobial Acyclic and Heterocyclic Dyes and Their Precursors for Dyeing and/or Textile Finishing Based on 2-N-Acylamino-4,5,6,7-tetrahydro-benzo[b]thiophene Systems

Abstract: A series of novel polyfunctionalized acyclic and heterocyclic dye precursors and their respective azo (hydrazone) counterpart dyes and dye precursors based on conjugate enaminones and/or enaminonitrile moieties were synthesized. The dyes and their precursors are based on 2-cyano-N-(3-cyano-4,5,6,7-tetrahydrobenzo[b]thiophen-2-yl)-acetamide, 2-ethoxycarbonyl-N-(3-cyano-4,5,6,7-tetrahydrobenzo[b]thiophen-2-yl)-acetamide or 2-phenylcarbamoyl-N-(3-cyano-4,5,6,7-tetrahydrobenzo[b]thiophen-2-yl)-acetamide systems as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Now, we have extended our synthetic program to the synthesis of otherwise inaccessible heterocyclic ring systems utilizing 1-naphthyl-2-cyanoacetamide (1) and PhNCS as keys starting materials. It is known that a great variety of reactants bearing the N-C-S fragment undergo cyclization on reaction with α-halocarbonyl compounds to afford thiazole, 2,3-dihydro-thiazole and thiazolidines moieties [23] which have been shown to exhibit local antitumor and antioxidant [24], antimicrobial [25], and antitumor activity [26]. Here, we describe a generally applicable extension of this synthetic approach; the base prompted reaction of the acidic methylene compound (1) with phenyl isothiocyanate in dry dimethylformamide at room temperature yields the non-isolable intermediate (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we have extended our synthetic program to the synthesis of otherwise inaccessible heterocyclic ring systems utilizing 1-naphthyl-2-cyanoacetamide (1) and PhNCS as keys starting materials. It is known that a great variety of reactants bearing the N-C-S fragment undergo cyclization on reaction with α-halocarbonyl compounds to afford thiazole, 2,3-dihydro-thiazole and thiazolidines moieties [23] which have been shown to exhibit local antitumor and antioxidant [24], antimicrobial [25], and antitumor activity [26]. Here, we describe a generally applicable extension of this synthetic approach; the base prompted reaction of the acidic methylene compound (1) with phenyl isothiocyanate in dry dimethylformamide at room temperature yields the non-isolable intermediate (3).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the mass spectrum showed molecular ion peak at m/z = 384.95 (M + ) corresponding to its molecular formula C 21 H 15 N 5 OS. A proposed reaction sequence involved an initial nucleophilic addition of the exocyclic amino group in aminopyrazole (11) to phenyl isothiocyanate giving (23) 5-Amino-N-(naphthalen-1-yl)-3-(phenylamino)-1H-pyrazole-4-carboxamide (11) has been diazotized in acetic acid with HCl and sodium nitrite at 0-5°C to yield non isolable pyrazoldiazonium salts (25). The attempted coupling with active methylene reagents resulted in direct formation of pyrazolo [3,4- (26) via cyclocondensation reaction which took place in situ under coupling reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…18,19) It has been reported that multi-component reactions (MCRs) can combine three or more components together in a single reaction vessel and produce final products with a minimum of synthetic time and effort 20) because they are no need to separate any reaction intermediate. 21) Such MCRs often result in high atomeconomy and high selectivity products.…”
Section: Resultsmentioning
confidence: 99%
“…The literature that covers the chemistry of cyanoacetamides has been limited. Derivatives of 2‐cyano‐ N ‐acetamide are tremendously important precursors in the synthesis of heterocyclic systems . The most approximate preparation of these compounds has been explained elsewhere .…”
Section: Introductionmentioning
confidence: 99%